Методологічні основи дослідження інноваційного потенціалу технологічного підприємництва в Україні - Бутенко, А.І.; Уманець, Т.В.; Гриневич, Л.В. (Економічний вісник Донбасу, 2017)
У статті викладено авторське бачення методології дослідження інноваційного потенціалу технологічного підприємництва. Означено процеси перебудови передових економік, що позначились на державних пріоритетах України. Обґрунтовано необхідність переходу України до економіки, яка базується на ефективному використанні інноваційного потенціалу технологічного підприємництва, в основу стійкої конкурентної переваги якого покладена інноваційна ідея. Визначено передумови становлення та успішного розвитку технологічного підприємництва. Надано авторське бачення сутності категорії «інноваційний потенціал технологічного підприємництва» на основі системного підходу з урахуванням структури взаємозв’язків між елементами системи технологічного підприємництва та з позиції стратегічного і оперативного управління. Визначено умови динамічного росту даного потенціалу. Кількісні та якісні параметри розвитку інноваційного потенціалу технологічного підприємництва запропоновано розглядати у рамках системи його індикаторів і характеристик, яка утворюється на базі двох підсистем: інноваційний кадровий потенціал технологічного підприємництва (професійно-технічний, науковий і дослідницький) та економіко-екологічний (інфраструктурно-виробничий, інвестиційно-фінансовий, інформаційний, ринковий та екологічний). Висунуто дві гіпотези відносно дослідження даного потенціалу, означено методи наукового пізнання та припущення для кожної з них. Визначено принципи побудови архітектури методологічних засад дослідження інноваційного потенціалу технологічного підприємництва в Україні (системності, урахування обліку взаємообумовленості функціонування складових системи технологічного підприємництва та компетентності). Рекомендовано кількісну оцінку рівня інноваційного потенціалу технологічного підприємництва здійснювати на основі інтегральних індикаторів. Приведено трьохступеневу структуру побудови даних інтегральних індексів, надано алгоритм їх розрахунку та методичний підхід до ідентифікації рівня інноваційного потенціалу технологічного підприємництва за допомогою оціночної шкали в рамках п’яти класів: критичний, низький, задовільний, середній та високий. Визначено потенційних споживачів отриманої інформації за даним методичним підходом. Запропоновано з метою активізації діяльності технологічного підприємництва розробити механізм формування, використання та розвитку інноваційного потенціалу технологічного підприємництва. В статье изложено авторское видение методологии исследования инновационного потенциала технологического предпринимательства. Дана характеристика процессов перестройки передовых экономик, оказавших влияние на государственные приоритеты Украины. Обоснована необходимость перехода Украины к экономике, базирующейся на эффективном использовании инновационного потенциала, в основу устойчивого конкурентного преимущества которого положена инновационная идея. Определены предпосылки становления и успешного развития технологического предпринимательства. Дано авторское видение сущности категории «инновационный потенциал технологического предпринимательства» на основе системного подхода с учетом структуры взаимосвязей между элементами системы технологического предпринимательства и с позиции стратегического и оперативного управления. Определены условия динамического роста данного потенциала. Количественные и качественные параметры развития инновационного потенциала технологического предпринимательства предложено рассматривать в рамках системы его индикаторов и характеристик, созданной на базе двух подсистем: инновационный кадровый потенциал (профессионально-технический, научный и исследовательский) и экономико-экологический (инфраструктурно-производственный, инвестиционно-финансовый, информационный, рыночный и экологический). Выдвинуты две гипотезы относительно исследования данного потенциала, определены методы научного познания и допуски для каждой из них. Определены принципы построения архитектуры методологических основ исследования инновационного потенциала технологического предпринимательства в Украине (системности, учета взаимообусловленности функционирования сложных систем технологического предпринимательства и компетентности). Предложено количественную оценку уровня инновационного потенциала технологического предпринимательства осуществлять на основе интегральных индикаторов. Приведена трехступенчатая структура построения этих интегральных индексов, дан алгоритм их расчета и методический поход относительно идентификации уровня инновационного потенциала технологического предпринимательства с помощью оценочной шкалы в рамках пяти классов: критический, низкий, удовлетворительный, средний и высокий. Определен круг потенциальных потребителей полученной информации согласно данному методическому подходу. Предложено с целью активизации деятельности технологического предпринимательства разработать механизм формирования, использования и развития инновационного потенциала технологического предпринимательства. The article outlines the author's vision of the methodology of researching the innovative potential of technological entrepreneurship. The processes of restructuring of advanced economies, which have affected the state priorities of Ukraine, are indicated. The necessity of transition of Ukraine to the economy, which is based on the effective use of innovative potential of technological entrepreneurship, is grounded on the basis of the stable competitive advantage of which the innovative idea is based. The preconditions of formation and suc- cessful development of technological entrepreneurship are determined. The author's vision of the essence of the category "innovative potential of technological entrepreneurship" is given on the basis of the system approach, taking into account the structure of interconnections between the elements of the technological entrepreneurship system and the position of strategic and operational management. The conditions of the dynamic growth of this potential are determined. Quantitative and qualitative parameters of the development of innovative potential of technological entrepreneurship are proposed to be considered within the framework of its system of indicators and characteristics, which is formed on the basis of two subsystems: innovative personnel potential of technological entrepreneurship (vocational, scientific and research) and economical and ecological (infrastructure, production, investment-financial, informational, market and environmental). Two hypotheses concerning the research of this potential are put forward, methods of scientific knowledge and assumptions for each of them are indicated. The principles of the construction of the architecture of the methodological foundations of the research of the innovative potential of technological entrepreneurship in Ukraine (systematic, accounting for the interdependence of the functioning of the components of the system of technological entrepreneurship and competence) have been determined. It is recommended that the quantitative assessment of the level of innovation potential of technological entrepreneurship is based on integrated indicators. The three-stage structure of data integral indexes is given, the algorithm of their calculation and the methodical approach to identifying the level of innovative potential of technological entrepreneurship with the help of an assessment scale within the framework of five classes are given: critical, low, satisfactory, medium and high. The potential consumers of the received information according to this methodical approach are determined. In order to intensify the activity of technological entrepreneurship, it is proposed to develop a mechanism for the formation, use and development of the innovative potential of technological entrepreneurship.